(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Pharmacogenomics has emerged as a useful tool in tailoring drug therapies, particularly in managing chronic diseases, where safety and efficacy over the long term are critical. Objective: This study aimed to establish pharmacogenomics’ effect on drug prescribing practices among medical practitioners managing chronic illnesses. Methodology: A cross-sectional survey was performed through a questionnaire structured in the physicians’, pharmacists’, and healthcare practitioners’ practicing clinics of Pakistan. Data were examined through SPSS version 26.0 utilizing descriptive and inferential statistical analysis. Results: The results indicated that while 76.2% of the participants knew about pharmacogenomics, 45.5% of them reported using it in prescribing. A clear majority recognized that it could restrict adverse drug effects (69.4%) and enhance therapeutic efficacy (72.8%), but asserted that they encountered barriers of training and infrastructure that limited its use. Conclusion: This study concludes that although pharmacogenomics is more familiar with its benefits in chronic disease management, its use in routine practice remains limited, which emphasizes the role of guideline-based implementation strategies, clinician education, and policy efforts.